PROFITABILITAS MEMODERASI UKURAN PERUSAHAAN, PERTUMBUHAN PENJUALAN, ARUS KAS BEBAS TERHADAP KEBIJAKAN HUTANG - Vivi, Vivi; Widyasari, Widyasari (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence about the effect of company size, sales growth, and free cash flow on debt policy with profitability as a moderating variable in non cyclicals sector companies listed in the Indonesia Stock Exchange during the period 2019-2021. This research used 90 samples were used with 30 companies using purposive sampling method and data processing techniques using multiple regression analysis and moderation regression analysis assisted by using E-views 10. The results of this research indicate that company size, sales growth, and profitability have a significant effect on debt policy, free cash flow does not have a significant effect on debt policy, profitability can moderate company size on debt policy, and profitability cannot moderate sales growth and free cash flow on debt policy.